Formulation of Coffee Extract as Polymeric Nanoparticles and Studying their Potential Biological Activities - Sharaf, Nouran (AUC Knowledge Fountain, 2021)
Coffee extract was prepared and optimized (by solvent extraction) and subsequently entrapped into PLGA nanoparticles using single emulsion-solvent evaporation method (using Design Expert software). Dynamic Light Scattering, Scanning Electron Microscope, Fourier Transform-Infrared Spectroscopy and Folin Ciocalteau assay were used to characterize the NPs and to aid in selecting the optimum formulation conditions. The optimized NPs were in-vitro evaluated for their antimicrobial (by agar-well diffusion method), antioxidant (by DPPH assay) and anticancer (by MTT assay) activities. Finally, the release rate study was conducted for the NP sample showing the highly promising results. The succeeded NP sample, in terms of the most desirable physicochemical characteristics and enhanced biological performance, was fabricated under strict conditions of emulsifier concentration, homogenization speed and duration and a certain initial drug : polymer ratio. The desirable physicochemical characteristics involved small particle sizes with an average of 318.60±5.65 nm; uniformly distributed within a narrow range (PDI of 0.074±0.015), with considerable stability (zeta potential of -20.50±0.52 mV) and the highest entrapment efficiency (85.92±4.01%). It showed an effectively encapsulated extract within the polymeric matrix (confirmed by the FT-IR spectrum). It showed a considerable amount of encapsulated total polyphenolics of 10.21±2.11 mg GAE/g sample. The highest antioxidant activity, antimicrobial and anticancer activities were shown, reporting a 90.08±0.19 % inhibition of DPPH, IC(50) to the MCF-7 cancerous cell lines of 29.40±1.10 μg/mL and 30% growth inhibition of Escherichia coli and 40% of Candida albicans. The in-vitro release study showed a biphasic release profile in both tested pH media, 7.4 and 5.5.